1995
DOI: 10.1021/np50119a008
|View full text |Cite
|
Sign up to set email alerts
|

Novel Withanolides from Jaborosa sativa

Abstract: Four new withanolides [1-4] have been isolated from the aerial parts of Jaborosa sativa. Jaborosalactones R [1], S [2], and T [3] contain a hemiketal (or ketal) ring formed between a 21-hydroxyl and a 12-ketone and the characteristic -lactone side-chain of the withanolides. Jaborosalactone U [4] possesses an epoxy-"y-lactone side-chain and was identified as the 24,25-epoxy analogue of trechonolide A [5]• Jaborosa Miers is a South American genus belonging to the Solanaceae that comprises about 23 different spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 13 publications
4
27
0
Order By: Relevance
“…Although epoxy-d-lactones and lactols are quite common among the withanolides, this did not appear to be the case for the g-lactone side chains. Jaborosalactone U (381) isolated from J. sativa (Argentina), is the only known example of a 24,25-epoxy-g-lactone (119). The (23R) configuration was originally proposed for this compound based on NOE data, however, more recently X-ray crystallography showed that the configuration is (23S) (Fig.…”
Section: Trechonolidesmentioning
confidence: 99%
“…Although epoxy-d-lactones and lactols are quite common among the withanolides, this did not appear to be the case for the g-lactone side chains. Jaborosalactone U (381) isolated from J. sativa (Argentina), is the only known example of a 24,25-epoxy-g-lactone (119). The (23R) configuration was originally proposed for this compound based on NOE data, however, more recently X-ray crystallography showed that the configuration is (23S) (Fig.…”
Section: Trechonolidesmentioning
confidence: 99%
“…caulescens yielded the withanolides 1 and 2. These two compounds resemble the structures of Jaborosalactona R, S and T (isolated from J. sativa [3]), with respect to the presence of the hemiketal function between C-21 and C-12, but differ in the substitution pattern of ring A and B.…”
Section: Resultsmentioning
confidence: 67%
“…Nicotra and co-authors (2006) reported the isomeric clorohydrin, jaborosalactone 37 (20) from Jaborosa rotacea, and jaborosalactone T (21) was isolated from Jaborosa sativa (synonym Trechonaetes sativa) collected in Argentina (Bonetto et al, 1995).…”
Section: Chlorinated Plant Steroidsmentioning
confidence: 99%
“…1 and 2, and the biological activities of plant chlorinated steroids are presented in Table 1. Physalis peruviana Withania somnifera and Acnistus breviflorus (Nittala et al, 1981;Bessalle and Lavie, 1992) Not studied (Bonetto et al, 1995) Not studied Tubocapsicum anomalum (Shingu et al, 1990) Not studied (Makino et al, 1995;Kawai et al, 1996) Not studied (Ripperger and Kamperdick, 1998) (Kawai et al, 1996) Not studied …”
Section: Chlorinated Plant Steroidsmentioning
confidence: 99%